De Stijl Busana Classic Elegant - Azizah, Silwi; Kencana, Mega; Aryadi, Mirda; Rahmat, Fadri (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
final project entitled “Grid in Motion: De Stijl Classic elegant Fashion” is a fashion design project that adopts De Stijl as the primary source of inspiration. De Stijl is a modern art movement that emphasizes simplicity through the use of horizontal and vertical lines, geometric forms, and a combination of primary and neutral colors. This concept is combined with the characteristics of classic elegant fashion, which is known for its neat, graceful, sophisticated, and timeless appearance. This project presents three categories of garments: ready to wear, ready to wear deluxe, and haute couture. These garments are created using semi-wool and lurik gerimis fabrics. The De Stijl concept is implemented through patchwork techniques to create geometric compositions, which are further enhanced using quilting techniques and bead embellishments arranged along horizontal and vertical lines. The creative process consists of three stages: exploration, design development, and realization. The resulting collection, Grid in Motion, consists of three designs: Linear Motion, Framed Rhythm, and Dynamic Composition. This project aims to create aesthetically pleasing and functional garments while demonstrating that the visual principles of De Stijl can be successfully applied to classic elegant fashion without diminishing its elegant and modern character.